OmniFind: Development of a Single Search Platform for Locally Stored Resources using VuFind® in a Closed Network Environment - Ummer, Rehana; Rajgoli, Iqbalahmad U. (Journal of Information and Knowledge, 2025)
The article describes the development of OmniFind, a centralised, single-search platform developed by the Indian Space Research Organisation Headquarters (ISRO HQ) Library using VuFind®, an open-source tool. The aim was to simplify access for users to resources that were downloaded by Library staff in response to user requests but remained stored on staff computers, making them inaccessible to others on the Intranet. OmniFind solves this problem by bringing all local resources into a single search platform within the secure Spacenet network and addresses a critical gap in library resource discovery. The article documents a practical and replicable solution enabling the discovery of local resources by providing step-by-step instructions as to how metadata can be created manually using a CSV file, how local resources can be indexed using Apache Solr, and how the user interface can be customised to meet the institutional requirements. It also highlights the challenges and solutions in setting up the system, which can now serve as a model for other libraries with similar needs. Future plans include using tools like Zotero and JabRef for easier data entry and adding more content using publisher APIs.